Desain dan Implementasi pada Pemesanan Hotel Berbasis Visual Studio Programming dan Database MySQL - Annisa, Baita Hikmah; Fadhilah, Siti Nur; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
Based on the research we have carried out on the development of Hotel Booking Applications based on Visual Studio and MySQL database, especially in creating user and user-oriented applications. This application is designed to provide a user friendly interface, so that it can make it easier for users to make hotel reservations. The application development process involves several database structures to manage hotel booking information, employee data, room data, guest data, check in and check out, as well as logic programming in the application for data processing. The results of developing this application are expected to provide satisfaction to users and users who have used the hotel booking application and show the level of user satisfaction in the speed of the hotel booking process.